Rationalization of Physico-chemical Properties of 1,3,5-Trisubstituted Aryls as Highly Selective PPARδ Agonist - Hemalatha, Rajaram; Manoj Kumar, Palanivelu; Chandra Mahajan, Suresh; Gopalrao Kaskhedikar, Sathish (Asian Journal of Chemistry, 2010)
To optimize the physiochemical properties of 1,3,5-trisubstituted aryls with high selective agonist activity on PPARδa quantitative structural activity relationship. Hansch approach was made using combination of various thermodynamic, electronic and spatial descriptors. Several regression expressions are obtained using multiple linear regression analysis. The best QSAR is further validated by leave-one-out cross validation method. The present studies reveal that for selective PPARδ agonist activity, modification at R4 and R5 substituted positions in molecule is more favourable and also electronic parameters play a key role in activity.